Literature Review : EFEK PHYSICAL ACTIVITY TERHADAP KEMAMPUAN KOGNITIF PADA ANAK ATTENTION-DEFICIT HYPERACTIVITY DISORDER (ADHD) - Dimas Arif Alfarisyi (2021)
Objective: To explore the effects of physical activity in children with Attention-Deficit Hyperactivity Disorder by reviewing journal, literature, article, and result of research on the topic. Methods: Researching articles by using Google Scholar, PubMed, and Science Direct with specific keywords in the period between 2012-2021. The articles obtained are adjusted to the data criteria in the form of the appropriateness of topics, research methods used, samples, interventions, instruments / parameters, and the results of each article with a total of 7 articles obtained. Result: The results of the study of 7 articles obtained improved cognitive scores of children with ADHD after receiving physical activity interventions with a certain dose. Conclusion: Physical activity can improve the cognitive abilities of children with Attention-Deficit Hyperactivity Disorder.